TOTAL BACTERIA IN BROILER FARMING WATER IN MENGESTA VILLAGE, PENEBEL DISTRICT, TABANAN REGENCY - Besung, I Nengah Kerta; Putra, I Putu Yasmanta Primarta; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana; Vol. 9 No. 2 Agustus 2017, 2017)
This study aim was to determine the total bacteriacountthat contaminated broiler farming water in Mengesta Village, Penebel District, Tabanan Regency. The water sample was collected from the source of the spring, water reservoir and chicken drinking pot. Each sample was taken as many as 100 ml and placed in the erlenmeyer glass. Water sampling was repeated 9 times infour-day sampling period. The data obtained were tested by analysis of variance and continued with least significant difference test. The results showed that total bacteria in chicken drinking pot(389,78 CFU / ml) was higher than in springs (247,89 CFU / ml), and shelter (171,33 CFU / ml). Its concluded that bacterial contamination occurred along the water flow.